Understanding Interpersonal Communication : making choices in changing times - West, Richard; Turner, Lynn H. (London : Thomson, 2006)
This paper investigates a number of questions concerning the relative advantages of the U.S. Mail versus electronic mail. Specifically, the paper asks: (1) what is the impact that E-mail has on the ways in which people communicate interpersonally in a visual presentation; (2) will E-mail replace such traditional forms of communication as greeting cards or are the two mediums simply different visual presentations; and (3) how can educators help students to understand the elements of the verbal, nonverbal code as they are manifest in both E-mail and the U.S. Mail's visual presentation of images? This paper reaches the conclusion that the difference between the two mediums is mainly one of texture, that is, how the message feels to the sender or receiver or how it makes them feel. The paper argues that "further humanization" of E-mail can be developed when students have knowledge and experience with both the technology and the "new" language code that is being developed to allow for increased interpersonal communication. An extensive chart examines in detail some of the relative advantages and disadvantages of the two mediums. (TB)
Includes Index.
Microfiche.
Keywords: Comparative Analysis; Electronic Mail; Higher Education; Interpersonal Communication; Language Usage; Letters (Correspondence); Student Adjustment; Technology Integration; Verbal Communication; Message Transmission; Opinion Papers; Speeches/Meeting Papers